Productivity and bioactivity of enokipodins A–D of Flammulina rossica and Flammulina velutipes. Issue 5 (3rd May 2020) - Tabuchi, Akiko; Fukushima-Sakuno, Emi; Osaki-Oka, Kumiko; Futamura, Yushi; Motoyama, Takayuki; Osada, Hiroyuki; Ishikawa, Noemia Kazue; Nagasawa, Eiji; Tokimoto, Keisuke
ABSTRACT: Enokipodins are antimicrobial sesquiterpenes produced by Flammulina velutipes in a mycelial culture medium. To date, enokipodin production has not been reported in other members of the genus Flammulina . Hence, in this study, the production of enokipodins A, B, C, and D by F. velutipes and F. rossica was investigated. Some strains of F. rossica were confirmed to produce at least one of the four enokipodins in the culture medium. However, some strains of F. velutipes did not produce any of the enokipodins. In an antibacterial assay using liquid medium, enokipodin B showed the strongest growth inhibitory activity against Bacillus subtilis among the four types of enokipodins. Enokipodin B inhibited the spore germination of some plant pathogenic fungi. Enokipodins B and D exerted moderate anti-proliferative activity against some cancer cell lines, and enokipodins A and C inhibited the proliferation of the malarial parasite, Plasmodium falciparum . Graphical abstract: uf0001 Productivity of enokipodins of some strains of F. velutipes and F. rossica and antibacterial activity of culture filtrate extract against B. subtilis .